Transcultural analysis of the effectiveness of a program to promote self-regulated learning in Mozambique, Chile, Portugal, and Spain - Rosário, Pedro (2015)
The current investigation aims at assessing the effectiveness of an intervention program designed to enhance self-regulated learning (SRL) strategies at the university level, with students from different cultural, linguistic, and educational backgrounds. The central tool of the program is a set of letters in which a fictional first-year student describes his experiences as an SRL student. The program was implemented in four universities in different countries and continents (Portugal, Spain, Chile, and Mozambique), with an experimental group and a comparison group at each university (263 students from experimental groups and 247 from comparison groups). Findings display the effectiveness of the program in enhancing a set of motivational variables related to the study process and the use of SRL strategies. Data were consistent across the different cultural and academic contexts in which the program was implemented. The implications of these findings for university administrators and faculty are discussed.